Inhibitory Effect of a Microecological Preparation on Azoxymethane/Dextran Sodium Sulfate-Induced Inflammatory Colorectal Cancer in Mice - Yu, Weinan; Zhang, Jie; Chen, Zhewen; Wang, Shuai; Ruan, Chuanxian; Zhou, Wenli; Miao, Mingyong; Shi, Hanping (Frontiers in Oncology, 2020)
This study aims to investigate the anti-tumor effect and the possible mechanism of a microecological preparation (JK5G) in mice. The mice treated with AOM/DSS were then randomly divided into the two groups model and JK5G groups and the blank control group was included. Fecal samples were used for liquid chromatography-mass spectrometry and 16S rRNA gene sequencing analyses to reveal metabolic perturbations and gut flora disorders to demonstrate the effects of JK5G. Compared with the mice in the control group, the weight and food intake of mice after JK5G treatment were both upregulated. Moreover, JK5G could inhibit the growth of colon tumors and prolong the survival rate of mice, as well as inhibit the levels of cytokines in serum. The proportions of lymphocytes, T cells, CD3+CD4+ T cells, and CD3+CD8+ T cells in the spleen of the JK5G mice were all significantly increased compared to those in the control group (p < 0.05). Similarly, compared with the model group, the proportions of lymphocytes, B cells, T cells, natural killer T cells, CD3+CD4+ T cells, and CD3+CD8+ T cells in the intestinal tumors of the JK5G mice were significantly increased (p < 0.05). Furthermore, 16S rRNA high-throughput sequencing data revealed that Alloprevotella in the JK5G group was significantly upregulated, and Ruminiclostridium, Prevotellaceae_UCG_001, and Acetitomaculum were significantly downregulated. Fecal and serum metabolite analysis detected 939 metabolites, such as sildenafil and pyridoxamine, as well as 20 metabolites, including N-Palmitoyl tyrosine and dihydroergotamine, that were differentially expressed between the JK5G and model groups. Integrated analysis of 16s rRNA and metabolomics data showed that there were 19 functional relationship pairs, including 8 altered microbiota, such as Ruminiclostridium and Prevotellaceae_UCG_001, and 16 disturbed metabolites between the JK5G and model groups. This study revealed that JK5G treatment was involved in the growth of colorectal cancer may be associated with the role of JK5G in improving the nutritional status of mice and regulating the tumor microenvironment by regulating the changes of intestinal microbiota and metabolite bands on different pathways.